THE ROLE OF TRANSACTIONAL LEADERSHIP STYLE IN ENHANCING EMPLOYEE WORK MOTIVATION: A CASE STUDY OF EMPLOYEES IN THE KUR BUSINESS UNIT AT PT BANK X KC PROBOLINGGO - Ony Ratri Suradinata Mandala; Achmad Sudiro; Ainur Rofiq (CV. Radja Publika, 2024)
The primary objective of this research is to uncover and understand the role of the transactional leadership style and to determine the outcomes of implementing the transactional leadership style by the leader of PT Bank X Branch Probolinggo in enhancing employee work motivation. This study employs a qualitative approach with a case study method. Data were obtained through interviews with employees in the KUR business unit of PT. Bank X Branch Probolinggo. Data collection techniques include observation, interviews, and documentation. Data analysis utilizes the Miles and Huberman model. The findings of this research indicate (1) The implementation of the transactional leadership style in this study has proven to motivate employees by the leader of PT Bank X Branch Probolinggo, namely through contingent rewards, (2) The implementation of the transactional leadership style in improving employee performance is effective, as evidenced by active management by exception and passive management by exception.